2017
DOI: 10.1177/1177180117700799
|View full text |Cite
|
Sign up to set email alerts
|

Māori University success: what helps and hinders qualification completion

Abstract: Māori (Indigenous New Zealand) university graduates are role models for educational success and are critical for the social and economic wellbeing of Māori whānau (extended family) and communities. In this study, Māori graduates ( N = 626) from all eight New Zealand universities participated in the Graduate Longitudinal Study New Zealand between July and December 2011. They were asked to describe factors that they found helpful or challenging to the completion of their qualifications. Graduates described a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 15 publications
7
20
0
Order By: Relevance
“…Pacific graduates in this study described having multiple inter-related obligations, including parenting, study and employment that impacted on course completion. This finding replicates that of previous GLSNZ research with Māori graduates showing that balancing these types of commitments puts students and their families under considerable pressure (Theodore, Gollop, et al, 2017). Moreover, research suggests that these commitments may disproportionately affect Pacific and Māori students compared to other students (Zepke et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pacific graduates in this study described having multiple inter-related obligations, including parenting, study and employment that impacted on course completion. This finding replicates that of previous GLSNZ research with Māori graduates showing that balancing these types of commitments puts students and their families under considerable pressure (Theodore, Gollop, et al, 2017). Moreover, research suggests that these commitments may disproportionately affect Pacific and Māori students compared to other students (Zepke et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The Graduate Longitudinal Study New Zealand (GLSNZ) is an ongoing, longitudinal project that, over a 10-year period, investigates the outcomes of graduates from all eight New Zealand universities (Tustin et al, 2012). Previous GLSNZ research has identified key helping and hindering factors for Māori university graduates (Theodore, Gollop, et al, 2017). In this study, we build on previous work by identifying what helped and hindered the course completion of hundreds of Pacific Island university graduates.…”
mentioning
confidence: 99%
“…The focus on giving back to others, and the notable absence of commentary about large salaries or opportunities for personal acquisition, fits with other research demonstrating the enduring collectivist values held by Māori (Houkamau & Sibley, 2017). It also aligns with literature describing drivers of success for Indigenous students as contributing to their community’s development (Theodore et al, 2017).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, overall STEM enrolment rates were about the same as most OECD countries (Norgrove and Scott 2017;. When broken down by ethnicity, the general trend is likewise apparent for Māori graduates, with 62% completing qualifications at bachelor degree level or above within five years of starting full-time study (Theodore et al 2017). However, in comparison to European and Asian students Māori were about half as likely to be studying STEM subjects as a proportion of overall enrolments (Table 1).…”
Section: Māori Student and Workforce Stem Capacitymentioning
confidence: 83%
“…Recent evidence suggests that academic barriers can be reduced by culturally responsive policies and strategies, integrated support services, support staff and programmes, and improved institutional practice (Theodore et al 2017). Science for Technological Innovation: Kia kotahi mai -Te Ao Putaiao me te Ao Hanagarau (SfTI-TAPTAH), one of Aotearoa's 11 NSCs, is developing an approach that seeks to translate such evidence into its programmes.…”
Section: Introductionmentioning
confidence: 99%